Interplay of surface polarization charge, dynamic electrical stimulation and compositional modification towards accelerated osteogenic response of NaxK1-xNbO3 piezo-bioceramics - Khare D.; Singh P.; Dubey A.K. (My University, 2025)
Bone remodeling processes involve endogenous bioelectrical signals such as piezoelectric charges. Moreover, external electrical stimulation helps in improving the healing capability of injured tissues by modulating the metabolic signaling pathways of cells. Towards this end, the present study reveals the influence of the combined action of electrostatic surface polarization charge and dynamic pulsed electrical stimulation alongwith compositional modification towards improving the osteogenic response of emerging piezo-bioceramics, sodium potassium niobate [NaxK1-xNbO3 (x = 0.2–0.8), NKN]. The dependence of crystal structure on compositions (x) was retrieved by Rietveld refinement and X-ray peak profile analyses. The surface charge, stored in the polarized (@ 25 kV at 500 °C) NaxK1-xNbO3 (x = 0.2, 0.5, 0.8) samples were measured to be 0.52, 0.50 and 0.47 μC/cm2, respectively, using thermally stimulated depolarized current (TSDC). X-ray photoelectron spectroscopy (XPS) survey scan spectra revealed that the polarization process does not alter the surface chemistry of NKN. Negatively charged surfaces are observed to accelerate early-stage adhesion of osteoblast-like cells which further results in enhanced spreading of adhered cells. Subsequently, the dynamic pulsed electrical stimulation of 1 V/cm with the pulse duration of 400 μs was applied, while the cells were being adhered on electrostatically charged surfaces. The quantitative and qualitative analyses revealed that the synergistic action of electrostatic surface polarization charge and dynamic pulsed electrical stimulation further accelerates cell proliferation and differentiation on negatively charged surfaces of Na and K-rich compositions of NKN. The mechanism of augmented cellular activity was analyzed using intracellular Ca2+ measurement. © 2022 Elsevier B.V.